Susceptibility of Eucalyptus Hybrid Clones to Botryosphaeria Canker in Uganda - Nakabonge, Grace; Namukasa, Evelyn; Tumwebaze, Susan B. (Journal of Sustainable Forestry, 2020)
The study assessed the susceptibility of the nine commonly grown Eucalyptus clones to Neofusicoccum species associated with Botryosphaeria canker in Uganda. The inoculation trials indicated that susceptibility of Eucalyptus hybrids differed significantly (p = .000), clones GU609, GU7, GC578, and GC796 exhibiting a higher tolerance than GC784, GC550, GU8, GC514, and GC540. The results further revealed that N. parvum was more pathogenic than N. kwambonambiense. The generated information can be exploited in sustainable forest management by expanding the growing of tolerant hybrids in areas with high Botryosphaeria canker disease pressure.
Keywords: Botryosphaeriaceae; Neofusicoccum; pathogenicity